2021
DOI: 10.1038/s41598-021-87468-5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of PCDD/Fs in PM2.5 from emission stacks and the nearby ambient air in Taiwan

Abstract: This study aimed to find the characteristics of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) in fine particulate matter from different stationary emission sources (coal-fired boiler, CFB; municipal waste incinerator, MWI; electric arc furnace, EAF) in Taiwan and the relationship between PM2.5 and PM2.5-bound PCDD/Fs with Taiwanese mortality risk. PM2.5 was quantified using gravimetry and corresponding chemical analyses were done for PM2.5-bound chemicals. Mortality risks of PM2.5 exposure and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
2
2
Order By: Relevance
“…The lowest TEQ reading of 3.85 ng I-TEQ/m³ was obtained during SC3, whereas SC4 yielded the highest measurement at 20.04 ng I-TEQ/m³ . Higher proportions of PCDFs over PCDDs was observed in this study which was contradictory to Pan et al [62] who reported higher proportions of PCDDs over PCDFs in the flue gases from CFB and MWI. Formation of low-chlorinated PCDDs (1,2,3,7,8-PeCDD, 1,2,3,4,7,8-HxCDD, 1,2,3,6,7,8-HxCDD and 1,2,3,7,8,9-HxCDD) possessed strong correlation and the chlorophenols were the important precursors of low-chlorinated PCDDs which were generated within the low chlorinated content [62].…”
Section: Optimal Fingerprint Profile For Pcdd/fs Congeners In Stack E...contrasting
confidence: 99%
See 1 more Smart Citation
“…The lowest TEQ reading of 3.85 ng I-TEQ/m³ was obtained during SC3, whereas SC4 yielded the highest measurement at 20.04 ng I-TEQ/m³ . Higher proportions of PCDFs over PCDDs was observed in this study which was contradictory to Pan et al [62] who reported higher proportions of PCDDs over PCDFs in the flue gases from CFB and MWI. Formation of low-chlorinated PCDDs (1,2,3,7,8-PeCDD, 1,2,3,4,7,8-HxCDD, 1,2,3,6,7,8-HxCDD and 1,2,3,7,8,9-HxCDD) possessed strong correlation and the chlorophenols were the important precursors of low-chlorinated PCDDs which were generated within the low chlorinated content [62].…”
Section: Optimal Fingerprint Profile For Pcdd/fs Congeners In Stack E...contrasting
confidence: 99%
“…Higher proportions of PCDFs over PCDDs was observed in this study which was contradictory to Pan et al [62] who reported higher proportions of PCDDs over PCDFs in the flue gases from CFB and MWI. Formation of low-chlorinated PCDDs (1,2,3,7,8-PeCDD, 1,2,3,4,7,8-HxCDD, 1,2,3,6,7,8-HxCDD and 1,2,3,7,8,9-HxCDD) possessed strong correlation and the chlorophenols were the important precursors of low-chlorinated PCDDs which were generated within the low chlorinated content [62]. The stack emissions presented certain similarities with an increasing chlorinated level, the content of the 2,3,7,8-PCDD congener increased but the content of 2,3,7,8-PCDF congener showed irregularities.…”
Section: Optimal Fingerprint Profile For Pcdd/fs Congeners In Stack E...contrasting
confidence: 99%
“…Among the EAFs, EAF-2 had a HCBD concentration of 441.6 ng/g, which was the next highest concentration after SCu. This high concentration of HCBD in EAF steelmaking could be caused by the presence of organic residues in scrap raw materials, such as rubber, cable wrapping, plastics, and polyvinyl chloride, which provide additional sources of chlorine for the unintentional formation and emission of HCBD 29 . Yang et al speculated that differences in the chlorine contents of raw materials and metal catalysts are important contributors to differences in the emissions of chlorinated organic pollutants 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The application of ambient meteorology, emissions, and atmospheric chemistry datasets through WRF-Chem modeling at a high spatial-resolution of 4.2 km 2 provides more granular insights into local PM 2.5 levels. Air quality improves slightly in the vicinity of TPP even in 2030 BAU due to differences in meteorology inputs between 2018 and 2030 and meteorology effects on secondary PM 2.5 formation downwind of TPP (Pan et al 2021 ); eliminating emissions from TPP in 2030 M&A results in larger and more widespread PM 2.5 reductions than those attributed to changing meteorology.…”
Section: Resultsmentioning
confidence: 99%